(untitled) (The Pakistan Development Review, 2003)
Access to clean drinking water and sanitation facilities have a direct positive impact on health through prevention of water-borne diseases, especially diarrhoeal morbidity of children. Lack of WES (Water and Environmental Sanitation) services and poor hygiene practices in Pakistan contribute significantly to the prevalence of diarrhoea, a major cause of infant death and children less than five years of age. The estimates show that about 30 percent of total deaths among children are attributed to diarrhoeal disease [Gallup (2001); UNICEF (2000)], and 4.1 years in life expectancy can be added if water borne diseases are eliminated [Ali and Haq (2003)]. Hence, reduction of diarrhoeal morbidity stands out as an important policy goal, which can ultimately lead to reduction in infant/child mortality. In this paper, we shall examine the relationship of WES interventions with that of the incidence of diarrhoea among children under age 10.